First genetic record of the non‐native muzzled blenny Omobranchus punctatus (Teleostei: Blenniidae) in the Atlantic Coast of Central and South America. Issue 3 (20th February 2020) - Cabezas, M. Pilar; Lasso‐Alcalá, Oscar M.; Xavier, Raquel; Jowers, Michael J.
Abstract: In this study we sequenced two mitochondrial (COI and 16S rRNA) and one nuclear (18S rRNA) gene fragment of an introduced muzzled blenny ( Omobranchus punctatus ) specimen collected from the Orinoco Delta (Gulf of Paria estuary) in Venezuela. This is the first genetic data generated for this species' introduced range in Central and South America, suggesting an introduction from the Indian Ocean.